Sustainable Development and Green Social Work in Indonesia: A Systematic Review - Putri, Risya Ananda; Raharjo, Santoso Tri; Resnawaty, Risna (UIN Sunan Kalijaga Yogyakarta, 2024)
Sustainable development and the role of social workers have emerged as interconnected concepts and essential components for enhancing societal welfare. Nevertheless, the comprehensive approach necessary to mitigate the adverse effects of development is frequently neglected, as the emphasis tends to be placed on profit-driven outcomes rather than on sustainable livelihoods. To address this gap, the current research aims to explore the intersection of green social work in Indonesia, which adopts a holistic perspective, and sustainable development, which is viewed as a long-term objective. A systematic literature review was conducted, resulting in the identification of approximately 17 relevant articles utilizing the PRISMA 2020 methodology. Through content analysis, the study revealed that the disparity in the sustainable development framework from the perspective of social work ethics arises from a predominant focus on economic activities at the expense of socio-environmental considerations. This finding indicates that political ecology influences the formulation of regulations by the state, which reflects neoliberal ideologies and contributes to challenges such as forest fires, environmental pollution, deterioration of freshwater quality, and the degradation of forest ecosystems. Despite the emergence of these negative consequences, several critical factors must be addressed to advance the principles of green social work. These include strengthening the foundational principles and roles of social workers and fostering stakeholder networks as a primary agenda for future development initiatives. This study advocates for the integration of the values and principles of green social work into all activities related to development and welfare by social workers. Keywords: Sustainable Development, Green Social Work, A Systematic Review, Social Workers, Indonesia Sustainable development and the role of social worker telah menjadi konsep integratif and sumber utama untuk peningkatan kesejahteraan. Namun, pendekatan holistik dalam implikasi negatif dari pembangunan cenderung terabaikan, karena lebih berorientasi kepada profit-oriented daripada kesejahteraan berbasis sustainable livelihoods. Untuk memetakan kesenjangan ini, riset ini hadir untuk mencari titik temu antara green social work sebagai pendekatan holistic dengan sustainable advancement sebagai konsep jangka panjang di Indonesia. Sistematika literatur review digunakan, dan berhasil menemukan topik sekitar 17 articles yang berhasil diekstraksi dengan metode PRISMA 2020. Berdasarkan konten analisis, studi menemukan bahwa kesenjangan konsep pembangunan berkelanjutan dari etika pekerja sosial muncul karena skema tersebut lebih condong pada aktivitas ekonomi daripada socio-environmental approaches. Hal ini mengindikasikan bahwa politik ekologi merupakan penyusunan regulasi negara sebagai ejawantah dari pengusung neoliberalisme, sehingga memicu kebarakan hutan, pencemaran lingkungan, kualitas air segar, dan keterbatasn fungsi hutan. Meskipun implikasi negatif tersebut telah berkembang, ada beberapa aspek penting yang perlu diubah dalam mempromosikan konsep green social work, yaitu prinsip dan peran pekerja sosial harus ditingkatkan dan membangun jaringan stakeholder menjadi agenda utama dalam mempromosikan pembangunan di masa depan. Studi ini merekomendasikan bahwa peran pekerja sosial harus menginternalisasikan nilai dan prinsip green social work dalam segala aktivitas yang berhubungan dengan pembangunan dan kesejahteraan. Kata kunci: Pembangunan Berkelanjutan, Tinjauan Sistematis, Pekerjaan Sosial, Indonesia